2001
DOI: 10.1149/1.1409545
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Characterization of Oxide Films Formed on Copper in Air

Abstract: Oxide layers thermally formed on copper have been studied using double sweep cyclic voltammetry in strongly alkaline electrolytes. It was found that the addition of 1 M LiOH in an electrolyte (6 M KOH) allowed perfect resolution of cathodic waves due to the reduction of Cu2O and CuO. Assignment of the two reduction waves has been achieved with the help of spectrophotometric techniques including X-ray photoelectron spectroscopy and X-ray diffraction; the cathodic wave appearing between −1.3 and −1.5 V (vs. Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 29 publications
9
71
0
1
Order By: Relevance
“…1 M KOH. 28,30 Copper hydroxyl oxides (Cu 2 (OH) 3 Cl and Cu(OH)Cl) are only stable at around pH 3.5 to 5.5, 3,31 while Cu 2 O is more stable in neutral to alkaline environments. 0.1 M Na 2 CO 3 is basic with a pH of 11.5, which resulted in different reduction potentials for paratacamite and cuprite.…”
Section: Resultsmentioning
confidence: 99%
“…1 M KOH. 28,30 Copper hydroxyl oxides (Cu 2 (OH) 3 Cl and Cu(OH)Cl) are only stable at around pH 3.5 to 5.5, 3,31 while Cu 2 O is more stable in neutral to alkaline environments. 0.1 M Na 2 CO 3 is basic with a pH of 11.5, which resulted in different reduction potentials for paratacamite and cuprite.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, copper-based nanomaterials have received attention because of their potential application in optoelectronic devices, catalysis and superconductors. CuO is a p-type semiconductor (E g ¼ 1.2 eV) with excellent photovoltaic, electrochemical, and catalytic properties [21][22][23][24]. Also, it is inexpensive, non-toxic, and readily available.…”
Section: Preparation and Characterization Of Cuo Nanoparticles Startimentioning
confidence: 99%
“…It suggested that copper oxide substance except Cu 2 O is also included in the Cu-oxide electrode with the oxidation temperature of 250°C. By double sweep cyclic voltammetry method (DSCV method), 33,34) CuO and Cu(OH) 2 in the Cu-oxide film were actually detected. The CuO contributes the potential ennoblement immediately after light irradiation.…”
Section: Surface Reactions Of the Electrode During Lightmentioning
confidence: 99%